Genetic basis of the resistance to Strongyloides venezuelensis (Nematoda, Rhabdiasidae) infection in mice (Mus musculus) - Marra, Nelson Mendes [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Amarante, Mônica R.V. [UNESP] (Sociedade Brasileira de Genética, 2007)
We investigated the resistance to Strongyloides venezuelensis primary infection of mice strains NIH (resistant) and C57BL/6 (susceptible) and the F1 and F2 offspring of crosses between these strains. The mice were infected with 2000 larvae and seven days later were sacrificed for parasite recovery and counting. There was no statistically significant (p > 0.05) sex effect on resistance. The F1 mice showed an intermediate mean number of parasites as compared to the parental NIH and C57BL6 strains. Out of 400 F2 mice, the 10% most resistant mice were infected with 21 to 97 parasites, while the 10% most susceptible mice were infected with 1027 to 1433 parasites. We also found that F2 mice with black fur (n = 72), the same color as the C57BL/6 susceptible parental strain, were more susceptible than white (n = 104) or gray furred (n = 224) mice. It is conceivable that some genes determining coat color are located on the same chromosome as where genes controlling helminth resistance.
Keywords: mice; Strongyloides venezuelensis; resistance; genetics